New times, old beliefs: Projecting the future size of religions in Austria - Anne Goujon; Vegard Skirbekk; Katrin Fliegenschnee; Pawel Strzelecki (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
Projecting the religious composition of the population is relevant for several reasons. It is a key characteristic influencing several aspects of individual behaviour, including marriage and childbearing patterns. The religious composition is also a driver of social cohesion and increased religious diversity could imply a more fragmented society. In this context, Austria finds itself in a period of transition where the long-time dominant Roman-Catholic church faces a serious decline in membership, while other groups, particularly the seculars and the Muslims, increase their influence. We project religions in Austria until 2051 by considering relative fertility rates, religion-specific net migration, and the rate of conversion between religions and transmission of religious beliefs from parents to children. We find that the proportion of Roman Catholics is likely to decrease from 75% in 2001 to less than 50% by the middle of the century, unless current trends in fertility, secularisation or immigration are to change. The share of Protestants is estimated to reach a level between 3 and 5% in 2051. The most uncertain projections are for those without religious affiliation: they could number as little as 10% and as many as 33%. The Muslim population - which grew from 1% in 1981 to 4% in 2001 - will, according to our estimates, represent 14 to 26% of the population by 2051. If current fertility trends remain constant, Islam could represent the majority religion for those below 15 years of age in 2051. Other religion categories are estimated to constitute 7-12% of the population by 2051. – – Die Struktur und Mitgliederzahlen der österreichischen Religionsgemeinschaften haben sich in den letzten Jahrzehnten deutlich verändert. Die römisch-katholische Kirche zählt zwar nach wie vor die meisten Mitglieder, ihre Zahl ist jedoch stark zurückgegangen. Dieselben Tendenzen lassen sich auch in der Evangelischen Kirche erkennen. Die Zahl der Muslime in Österreich sowie der Personen ohne Religionsbekenntnis hat dagegen stark zugenommen. Was bringen die nächsten Jahrzehnte in Hinblick auf die Größe und Altersstruktur der Glaubensgemeinschaften in Österreich? In dieser demographischen Studie wurden Zahlen aus den Volkszählungen von 1981 bis 2001 analysiert. Es wurden die Entwicklung der Einund Austritte, das Fertilitätsverhalten der unterschiedlichen Religionsgemeinschaften sowie die Migration der letzten Jahrzehnte betrachtet. Schließlich wurden alternative Szenarien für die zukünftige Struktur der Glaubensgemeinschaften in Österreich bis zum Jahr 2051 berechnet.
Keywords: 300; Austria; religion; projections; Catholics; secularization; Muslim; migration; Religion; Katholizismus; Islam; Prognose; Bevölkerungsentwicklung; Internationale Wanderung; Österreich